Synthesis of Silica-Silver Core-Shell Nanoparticles and Catalytic Effect - Mun, Sangmi; Yoon, Binna; Hwi Cho, Bum; Bae Ko, Weon (Asian Journal of Chemistry, 2012)
Silica nanoparticles were synthesized using the Stöber's method under ultrasonic condition at room temperature. Silver nanoparticles were prepared by reacting an aqueous silver nitrate solution with glucose and poly(vinyl alcohol) (PVA) under microwave condition. 3-Mercaptopropyl trimethoxysilane (MPTMS) and 3-aminopropyl trimethoxysilane (APTMS) were used as a linker to combine the silica and silver nanoparticles. The synthesized silica-silver core-shell nanoparticles were characterized by X-ray diffraction, scanning electron microscopy and UV-VIS spectroscopy. UV-VIS spectroscopy was used to monitor the effect of the synthesized silica-silver core-shell nanoparticles as a catalyst for reducing various nitrophenols, such as 2-nitrophenol, 3-nitrophenol and 4-nitrophenol.